Changes in ankle and foot kinematic after fixed-bearing total ankle replacement. (May 2022) - Deleu, Paul-André; Naaim, Alexandre; Chèze, Laurence; Dumas, Raphaël; Devos Bevernage, Bernhard; Birch, Ivan; Besse, Jean-Luc; Leemrijse, Thibaut
Abstract: Ankle osteoarthritis is a chronic debilitating disease marked by cartilage breakdown, pain and significant biomechanical impairment of the entire lower limb. Total ankle replacement (TAR) has been encouraged during the last decade as it has the potential to maintain the existing pre-operative ankle range of motion and to protect the more distally located joints of the foot. Three-dimensional gait analysis using a multi-segment foot model can provide an objective analysis of TAR for the treatment of end-stage ankle osteoarthritis. Thirty-six patients suffering from post-traumatic end-stage ankle osteoarthritis were evaluated before and after TAR. A four-segment kinematic foot model was used to calculate intrinsic foot joint kinematics during gait. Spatio-temporal parameters were also assessed. Kinematic results were compared to a control group of asymptomatic subjects. Differences in waveform patterns were mainly limited to dorsi-/plantarflexion inter-segment angles. At loading response, the Shank-Calcaneus plantarflexion angles as well as the Calcaneus-Midfoot dorsiflexion angle increased slightly in post-operative condition. During propulsion, an increase in Hallux-Metatarsus dorsiflexion angle was observed. Pain improved after surgery as supported by increased spatio-temporal parameters. While multi-segment foot and ankle kinematics were improved, they remained impaired compared to control values. This study confirms that TAR maintains the residual pre-operative range of motion after surgery from midstance to propulsion. Furthermore, the results suggest that the kinematic behavior of the foot joints distal to the affected ankle joint also improves post-operatively. The outcome of this study further emphasizes the clinical relevance of multi-segment foot modeling when assessing the outcome of TAR.